Chicken Egg Proteins and Derived Peptides with Antioxidant Properties - Benedé, Sara (Foods, 2020)
In addition to their high nutritional value, some chicken egg proteins and derivatives such as protein hydrolysates, peptides and amino acids show antioxidant properties which make them prominent candidates for the development of functional foods, drawing attention to both the food and biopharmaceutical industries. This review summarizes current knowledge on antioxidant activity of chicken egg proteins and their derived peptides. Some egg proteins such as ovalbumin, ovotransferrin and lysozyme from egg white or phosvitin from yolk have shown antioxidant properties, although derived peptides have higher bioactive potential. The main process for obtaining egg bioactive peptides is enzymatic hydrolysis of its proteins using enzymes and/or processing technologies such as heating, sonication or high-intensity-pulsed electric field. Different in vitro assays such as determination of reducing power, DPPH and ABTS radical-scavenging activity tests or oxygen radical absorbance capacity assay have been used to evaluate the diverse antioxidant mechanisms of proteins and peptides. Similarly, different cell lines and animal models including zebrafish, mice and rats have also been used. In summary, this review collects all the knowledge described so far regarding egg proteins and derived peptides with antioxidant functions.